2015
DOI: 10.1093/femsle/fnv073
|View full text |Cite
|
Sign up to set email alerts
|

Determination of single nucleotide variants in Escherichia coli DH5α by using short-read sequencing

Abstract: Escherichia coli DH5α is a common laboratory strain that provides an important platform for routine use in cloning and synthetic biology applications. Many synthetic circuits have been constructed and successfully expressed in E. coli DH5α; however, its genome sequence has not been determined yet. Here, we determined E. coli DH5α genome sequence and identified genetic mutations that affect its phenotypic functions by using short-read sequencing. The sequencing results clearly described the genotypes of E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
5
12
0
Order By: Relevance
“…Under aerobic conditions, strain DH5a was predicted to be the best producer for the most constructs (568/3,983 or 14% of constructs) due to its inherent high expression of the biosynthetic pathways for tyrosine (Y) and phenylalanine (F) (amino acids that are often small fractions of the proteome) followed by BL21 (473/3,983 or 12% constructs) for similar reasons. This result aligns well with the fact that DH5a is often preferred and used in cloning applications (Taylor et al, 1993, Song et al, 2015) and BL21 is popular for expression of recombinant proteins (Robichon et al, 2011, Marisch et al, 2013). …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Under aerobic conditions, strain DH5a was predicted to be the best producer for the most constructs (568/3,983 or 14% of constructs) due to its inherent high expression of the biosynthetic pathways for tyrosine (Y) and phenylalanine (F) (amino acids that are often small fractions of the proteome) followed by BL21 (473/3,983 or 12% constructs) for similar reasons. This result aligns well with the fact that DH5a is often preferred and used in cloning applications (Taylor et al, 1993, Song et al, 2015) and BL21 is popular for expression of recombinant proteins (Robichon et al, 2011, Marisch et al, 2013). …”
Section: Resultssupporting
confidence: 87%
“…For example, the model of E. coli BL21 is unable to produce acrylic acid from heterologous pathways 23 and 24 (Data S4, Heterologous aerobic and anaerobic tabs) because it lacks N-acetylglucosamine kinase. Likewise, DH5a cannot make 3-hydroxypentanoic acid via a predicted heterologous route (pathway 223) due to the lack of homocysteine S-methyltransferase encoded for by mmuM (Song et al, 2015). A histogram of differential yield by pathway in each strain is given in Figure S4.…”
Section: Resultsmentioning
confidence: 99%
“…Several DH5α markers have been characterized previously: deoR , originally thought to be defective and therefore responsible for the high transformability of DH5α (3), is in fact a wild type (4); luxS is defective (5); and the rfbC1 allele is actually a frameshift in rfbD (6). Numerous other features can be deduced from the genome sequence of its ancestor, DH1 (7).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Numerous other features can be deduced from the genome sequence of its ancestor, DH1 (7). A whole-genome shotgun assembly (WGA) of DH5α, based on short reads and comprising 89 contigs, revealed additional variants (6). Although the characteristic deletion Δ( argF-lac ) 169 was originally determined to be 97 kb in length (8), the WGA study (erroneously, we find) inferred a shorter length of 85 kb, with the cynS-mhpC region not part of the deletion (6).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Seven commonly used strains in biotechnology applications include K-12 MG1655, K-12 W3110, K-12 DH5a, BL21, C, Crooks, and W. It has been shown that particular strains are better suited for different applications (Monk et al, 2016). For example, DH5a is often preferred in cloning applications (Song et al, 2015;Taylor et al, 1993), while BL21 is often preferred for expression of recombinant proteins (Marisch et al, 2013a;Robichon et al, 2011). It has also been shown that choice of host strain for production of a given compound can significantly impact production titers (Na et al, 2013).…”
Section: Introductionmentioning
confidence: 99%